Pengaruh Loan to Deposit Ratio dan Debt to Equity Ratio terhadap Return on Assets pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2021–2025 - Nur Ismi Khalifah; Aldy Agustian (Journal of Applied Accounting, 2026)
This study analyzes the effects of the Loan-to-Deposit Ratio (LDR) and Debt-to-Equity Ratio (DER) on Return on Assets (ROA) in banking companies listed on the Indonesia Stock Exchange during the 2021–2025 period. Using a quantitative approach and an explanatory research design, the sample comprises 30 banking companies selected through purposive sampling, yielding 150 observations. The data were analyzed using multiple linear regression in JASP software. The results show that the Loan-to-Deposit Ratio (LDR) has a positive but insignificant effect on Return on Assets (ROA) (sig. = 0.189), whereas the Debt-to-Equity Ratio (DER) has a negative and significant effect on Return on Assets (ROA) (sig. = 0.000). The model feasibility test indicates that the regression model is appropriate for analysis, with an F-value of 12.690 and a significance level of 0.000. The coefficient of determination (R²) of 0.147 indicates that 14.7% of the variation in Return on Assets (ROA) can be explained by the Loan-to-Deposit Ratio (LDR) and Debt-to-Equity Ratio (DER), while the remaining 85.3% is influenced by other factors outside the scope of this study. The findings suggest that the profitability of banking companies during the 2021–2025 period is more strongly influenced by capital structure management than by credit distribution activities. Therefore, banking companies should maintain an optimal balance between debt utilization and profitability to achieve sustainable financial performance. Keywords: Return on Assets; Loan-to-Deposit Ratio; Debt-to-Equity Ratio; Profitability; Banking.